Sistem Informasi PPDB Online SMPIT Harapan Mulia Palembang Menerapkan Metode Extreme Programming (XP) - Rozzi, Muhammad Hadad AR; Damayanti, Nita Rosa (LPPM STIKOM Tunas Bangsa, 2024)
Admission of New Students (PPDB) is the process of accepting prospective new students which is carried out by state and private educational institutions every year. The Ministry of Education and Culture continues to encourage every educational institution to be able to adapt to technological advances, one of which is the process of accepting new students. Harapan Mulia Palembang Integrated Islamic Junior High School (SMPIT) is a private educational institution in the city of Palembang, providing education at junior high school level. The process of accepting new students at SMPIT Harapan Mulia Palembang is still carried out using the conventional method, which has several disadvantages such as being limited by distance because prospective students have to come to school to register, damage and loss of registration data. To support the process of accepting new students to be more efficient, the author built a website-based online PPDB information system. This research was conducted at SMPIT Harapan Mulia Palembang, the system development method that the author uses is Extreme Programming (Xp). With this website-based online PPDB information system, students no longer need to come to school to register, the registration process can be done anywhere and at any time. Apart from that, with this system, it is easier for SMPIT Harapan Mulia Palembang to manage registration data for prospective students.